2020
DOI: 10.1111/eea.12948
|View full text |Cite
|
Sign up to set email alerts
|

Antennal sensory organs and glands of the harlequin ladybird, Harmonia axyridis

Abstract: Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) is a sub-cosmopolitan species. Native to Asia, it has been released during the 20th century for classical and augmentative biological control of several herbivorous insects, mostly aphids and coccids. Despite its recognized positive impact on biological control, H. axyridis is now considered among the most dangerous invasive species in Europe and in most places where it has established. This is mostly due to its ability to reduce the populations of native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 75 publications
9
28
0
Order By: Relevance
“…Most chemosensory genes did not exhibit sex-specific nor sex-biased expression. This is consistent with recent description of antennal morphology that did not reveal relevant sexual dimorphism in H. axyridis , neither for the antennal general structure, nor for the types of sensilla and their abundance [ 33 ]. However, this does not preclude that the significance of the perceived odors may differ between males or females.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most chemosensory genes did not exhibit sex-specific nor sex-biased expression. This is consistent with recent description of antennal morphology that did not reveal relevant sexual dimorphism in H. axyridis , neither for the antennal general structure, nor for the types of sensilla and their abundance [ 33 ]. However, this does not preclude that the significance of the perceived odors may differ between males or females.…”
Section: Discussionsupporting
confidence: 93%
“…Behavioural and electrophysiological experiments demonstrated that H. axyridis responds to volatile semiochemicals [ 1 , 31 , 32 ]. Additionally, various types of antennal chemoreceptor sensilla (notably basiconica, chaetica, and grooved peg) have been recently characterized [ 33 ]. Therefore, understanding the molecular basis of H. axyridis chemosensory reception, in particular olfaction, is likely to provide new information to increase the efficacy of this predator in biological control or to reduce its populations in those areas where H. axyridis has become a concern for local biodiversity [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is thought that ladybird maxillary palps are the most adequate structures for the perception of nonvolatile molecules [100], our results suggest a possible role of antennal contact in sugar detection. Possibly, the long sensilla chaetica that are positioned in H. axyridis at the tip of the antenna may be involved in the perception of such nonvolatile molecules [33]. Our analysis also revealed the presence of candidate receptors for CO 2 in H. axyridis antennae.…”
Section: Discussionmentioning
confidence: 62%
“…Sensilla basiconica are responsible for carbon dioxide detection in D. melanogaster [12]. These sensilla are present and abundant in male and female H. axyridis antennae [33]. Although this kind of sensilla is known to be involved in the detection of a plethora of molecules in insects, including volatile molecules, it is possible that CO 2 detection is mediated by such sensilla in H. axyridis .…”
Section: Discussionmentioning
confidence: 99%
“…The chemical ecology of entomophagous insects is addressed focusing both on the functional morphology of antennal sensilla and on the exploitation of semiochemicals to improve predator efficacy. Sevarika et al (2021) investigated the antennal sensilla of Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) using scanning and transmission electron microscopy. Various types of sensilla (chemoreceptors, mechanoreceptors, and thermo‐hygroreceptors) and their distributions are described.…”
mentioning
confidence: 99%